2010
DOI: 10.3109/13682820902818870
|View full text |Cite
|
Sign up to set email alerts
|

Communicative and linguistic development in preterm children: a longitudinal study from 12 to 24 months

Abstract: Findings suggest that despite the significant biological risk engendered by premature birth, early communicative and linguistic development appears to proceed in a relatively robust fashion among preterm children, with tight relations across communicative domains as in full-term children. Employing both chronological and corrected gestational age criteria in the evaluation of preterm children's abilities may provide important information about their progress in language acquisition. This may be especially impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 48 publications
1
12
1
2
Order By: Relevance
“…Regarding the Hearing and Language quotient, it is relevant to note that most of the infants did not present an index of delay, defined as a score < 1 DS. This result is unexpected and is not in line with previous studies (Cattani et al, 2010;Sansavini et al, 2011;Ballantyne et al, 2016;Ionio et al, 2016;Cheong et al, 2017;de Jong et al, 2017;Lean et al, 2018;Pisoni et al, 2018), in which preterm infants have shown worse linguistic development than FT ones. A possible explanation could regard the time of assessment: all the previously mentioned studies mainly focused on the 2nd year postpartum, while the present study focused on the 1st year postpartum.…”
Section: Discussioncontrasting
confidence: 95%
“…Regarding the Hearing and Language quotient, it is relevant to note that most of the infants did not present an index of delay, defined as a score < 1 DS. This result is unexpected and is not in line with previous studies (Cattani et al, 2010;Sansavini et al, 2011;Ballantyne et al, 2016;Ionio et al, 2016;Cheong et al, 2017;de Jong et al, 2017;Lean et al, 2018;Pisoni et al, 2018), in which preterm infants have shown worse linguistic development than FT ones. A possible explanation could regard the time of assessment: all the previously mentioned studies mainly focused on the 2nd year postpartum, while the present study focused on the 1st year postpartum.…”
Section: Discussioncontrasting
confidence: 95%
“…Furthermore, to explore more thoroughly our data, group comparisons were also performed by controlling for child chronological age, but no significant differences emerged as well. The choice of performing this kind of control was motivated by recent literature suggesting that employing both corrected and chronological age criteria could provide more complete information and help clinicians to distinguish children who can be at risk of language delays from those who are more likely to catch up with their initial delays [ 57 ]. Moreover, putting aside the considerations on the use of age correction for low-risk preterm children, the inclusion of chronological age as a covariate allowed us to control for slight age differences in all children participating in the study.…”
Section: Discussionmentioning
confidence: 99%
“…En el presente trabajo se comprobaron, en un grupo de prematuros con riesgo de daño cerebral perinatal sometidos a Terapia Neurohabilitatoria, los beneficios específicos sobre la adquisición del lenguaje derivados del entrenamiento ofrecido a los padres para aplicarlo con sus bebés en el primer año de vida y de forma sostenida durante este tiempo. Como se señaló en la introducción de este artículo, los estudios comparativos acerca de la adquisición temprana del lenguaje en bebés prematuros y de término, realizados generalmente en pre-escolares y escolares, han reportado hallazgos controversiales; por un lado, unos reportan un retraso en sus habilidades de lenguaje, comparados con bebés nacidos a término (Sansavini et al, 2006;Foster-Cohen et al, 2007;Kern & Gayrau, 2007;Ortiz-Mantilla et al, 2008;Wolke et al, 2008;Guarini et al, 2009;Stolt et al, 2009;Stolt et al, 2011); por otro lado, otros no han encontrado diferencias significativas al comparar ambos grupos (Cattani et al, 2010;Pérez-Pereira & Resches, 2011) cuando se hace una corrección de la edad y se iguala el nivel cognoscitivo. Es difícil decidir cuál de estos dos tipos de hallazgos es el correcto, pero lo que sí sugieren los resultados del presente trabajo es que es posible encontrar puntuaciones normales cuando se utilizan pruebas estandarizadas y se lleva a cabo la corrección por la edad, teniendo una variable interventora en el proceso.…”
Section: Discussionunclassified
“…Mientras algunos estudios han encontrado que los bebés prematuros tienen un retraso en sus habilidades de lenguaje comparados con bebés nacidos a término (Magill-Evans & Harrison, 1999;2001;Sansavini, Guarini, Alessandroni, Faldella, Giovanelli, & Salvioli, 2006;Foster-Cohen, Edgin, Champion, & Woodward, 2007;Kern & Gayrau, 2007;OrtizMantilla, Choudhury, Leevers, & Benasich, 2008;Wolke, Samara, Bracewell, & Marlow, 2008;Guarini et al, 2009;Stolt, Haataja, Lapinleimu, & Lehtonen, 2009;Stolt, Lehtonen, Haataja, & Lapenleimu, 2011), en otros no se han encontrado diferencias significativas al comparar ambos grupos (Menyuk et al, 1991;Cattani et al, 2010;Pérez-Pereira & Resches, 2011) cuando se hace una corrección de la edad y se iguala el nivel cognoscitivo.…”
Section: Introductionunclassified